Simulation and experimental study of local high frequency resistance distribution in proton exchange membrane fuel cells under steady and dynamic conditions - Xin Zhan; Jiaqi Sun; Feng Ding; Xiaozhi Xu; Wei Song; Zhigang Shao (Heliyon)
Proton-exchange membrane (PEM) dry–wet variation during PEM fuel cell (PEMFC) operation markedly affects PEMFC lifespan. Therefore, deeper insights into the mechanical degradation mechanism of PEM require analysis of the membrane dry–wet change process. The stress changes caused by PEM dry–wet variations may induce mechanical failure. In practice, although high-frequency resistance (HFR) is often used to indirectly characterize PEM dry–wet degrees, numerical simulation can effectively analyze the mass transfer inside a PEMFC for parameters that are difficult to measure directly experimentally (such as membrane water content). Additionally, three-dimensional (3D) model validation requires more comprehensive experimental methods. In this study, we validate the simulated resistance distribution results through local electrochemical impedance spectroscopy. We also discuss the mass- and heat-transfer distribution characteristics under different current densities and analyze the influence of these characteristics on local HFR distribution variations. The calculated HFR distribution results show a certain degree of agreement with the experimental results. Due to the membrane self-humidification effect, the position of the minimum HFR value shifts upstream of the cathode at a high current density. The observed change in membrane stress results from variations in membrane water and temperature distributions with changes in current density. Steady-state HFR distribution analysis to uncover the membrane dry–wet variations caused by load changes—which would affect the HFR distribution changes—reveal that the HFR at the air outlet and the membrane dry–wet variations are more pronounced than at other locations due to the influence of reaction rate and gas velocity. Overall, this study demonstrates that 3D simulations can reliably predict the local HFR distribution of PEMFCs, enabling membrane stress variation analysis and providing guidance for fuel cell design and operation.